QUALITATIVE AND QUANTITATIVE STUDY OF OENOTHERA ROSEA TANINOS L ' HERO . EX AITON - Kasay, M. I. (2013)
The present study aims at evaluating the polyphenolic compounds of plant Oenothera rosea L' Hér. Ex Aiton in branches and leaves of five different methods. Phytochemical analysis for the abundance of tannins which are of great industrial importance is determined. It identifies and classifies tannins Oenothera rosea L' Hér. Ex Aiton , finding the presence of hydrolysable tannins and condensed . Deepened in valuing different types of tannins found , using methods Lowenthal and Folin - Ciocalteu for hydrolyzable tannins Stiasny and Technique Proanthocyanidin for condensed tannins using the UV method for the determination of both tannins in aqueous extracts and ethanol , the ethanol extracts being those with greater extracting power.